What is the inverse of **`f(x) = 1/(x - 2) + 3`**

### 1 Answer | Add Yours

The inverse of the function `f(x) = 1/(x - 2) + 3` has to be determined. For a function f(x), the inverse `f^-1(x)` is related by `f(f^-1(x)) = x`

For `f(x) = 1/(x - 2) + 3`

`f(f^-1(x)) = 1/(f^-1(x) - 2) + 3 = x`

=> `1/(f^-1(x) - 2) = (x - 3)`

=> `1/(x - 3) = (f^-1(x) - 2)`

=> `f^-1(x) = 1/(x - 3) + 2`

**The inverse of `f(x) = 1/(x - 2) + 3` is **`f^-1(x) = 1/(x - 3) + 2`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes